Following vibronic coherence in Furan with AttoXAFS - Severino, S.; Ziems, K. M.; Reduzzi, M.; Summers, A.; Sun, H. W.; Chien, Y. H.; Gräfe, Stefanie; Biegert, J. (Optics InfoBase Conference Papers, 2022)
We apply attosecond time-resolved carbon K-edge spectroscopy to simultaneously follow the coherent evolution and interplay of electronic and nuclear wavepackets after strong-field excitation of furan and retrieve their configurations along the ultrafast nonadiabatic relaxation pathways.
CRIS-Team Scopus Importer:2023-04-20